PENDAPATAN ASLI DAERAH (PAD) DI KOTA SURAKARTA (TAX ON LOCAL REVENUE IN SURAKARTA) - Pramesti, Hernawati; Nugraha, Basuki (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study about Local Revenue. This study uses secondary data with a population of all reports on the realization of advertisement tax, parking tax, Land and Property Tax and Surakarta Local Revenue in 2013-2017. Sampling uses a purposive sampling method and the data analysis technique used is t test, F test, and test the coefficient of determination (R2). The results of this study for the t test show the results that the advertisement tax, parking tax, and the Land and Property Tax variables affect Local Revenue, the F test results indicate advertisement tax, parking tax and the Land and Property Tax influence jointly on Local Revenue.